Maternal Milk Orchestrates the Development of Infant Gut Microbiota: Implications for Health and Future Research Directions - Ran Wang; Siyuan Sun; Qi Zhang; Guanglei Wu; Fazheng Ren; Juan Chen (Research)
Human breast milk serves as a vital source of nutrition for infants, and it also plays a critical role in shaping the infant gut microbiota and establishing intestinal homeostasis. This process substantially impacts immune function, neurodevelopment, and overall health. The noninvasive nature of breast milk collection makes it an ethical and accessible area for research, positioning it as a key focus for future studies. These future directions include the identification of novel bacteria combination, the establishment of comprehensive databases on infant microbiota, and the use of computational models to predict interactions between breast milk components and the gut microbiome. Additionally, the creation of diverse biological models and the establishment of infant stool banks will further enhance understanding of host–microbiome interactions and support disease prevention strategies.